Modelling Community Building Through Working Online. - Trinidad, Sue; Fox, R. (2006)
The University of Hong Kong provides on-going education for teachers and education professionals within the Faculty of Education through a Masters degree in Information Technology in Education or MSc[ITE]. The MSc[ITE] offers a flexible modular structure enabling students to progress according to their own pace. The course is delivered in a face-to-face mode supplemented by an online course room - Interactive Learning Network (ILN) which supports collaborative learning. ILN is a community-building environment designed to scaffold virtual education communities of practice where teachers and students work together as teams and engage in reflective, collegial patterns of work. ILN facilitates both cognitive as well as social scaffolding, which enables educators and students to become progressively more involved in the community and to sustain their commitment and interests. This environment is designed to support academic programmes that rely heavily on pedagogies that emphasize the emergence and growth of autonomous collaborative learning, rather than teacher-directed delivery of learning materials. This paper describes and analyses community building online in the foundation module for the MSc[ITE] and introduces models to assist in the design and evaluation of online learning communities.